Mapping Contentious Collective Emotions in a Populist Democracy: Duterte's Push for Philippine Federalism - Montiel, Cristina Jayme (Archīum Ateneo, 2020)
This article analyzes collective emotions toward political change in a populist democracy. Taking the federalization of the Philippines led by President Rodrigo Duterte as an exemplar case, we extend prevailing scholarship which focuses on populist leaders' electoral discourse by examining the affective landscape of the populist public in a postelectoral context. Utilizing a sequential mixed-methods design, we algorithmically classify the stance and sentiment valence of 18,535 Facebook comments about federalism, then we reflexively identify collective emotions based on major discursive storylines across each stance-sentiment intersection. Our integrated analysis reveals collective feelings of (1) hope and euphoria and (2) vindictive contempt among supporters of Duterte's federalism, while detractors of the campaign express (3) derisive amusement and (4) fear and skepticism. Two of these public emotions may be idiosyncratic to Global South populisms: public fear and president-invested salvific hope. We discuss the implications of our findings along themes of emotional polarization in a populist democracy, linking political affect with democratic participation through social media.